Adiponitrile at 100 K. Issue 11 (17th October 2017) - Seidel, Rüdiger W.; Goddard, Richard; Nöthling, Nils; Lehmann, Christian W.
Abstract : In the structure of adiponitrile, a key intermediate in the synthesis of the polyamide Nylon 66, at 100 K, the molecule adopts an exact C i ‐symmetric gauche – anti – gauche conformation of the C—C—C—C skeleton about an inversion centre. The molecules are densely packed, with short contacts between the α‐H and nitrile N atoms. Abstract : Adiponitrile, C6 H8 N2, is a key intermediate in the synthesis of the polyamide Nylon 66 and is produced industrially on a large scale. We have determined the crystal and molecular structure of adiponitrile by single‐crystal X‐ray analysis at 100 K, a suitable crystal (m.p. 275 K) having been grown from the melt at low temperature. The compound crystallizes in the monoclinic space group P 21 / c with Z = 2. In the crystal structure, the molecule adopts an exact C i ‐symmetric gauche – anti – gauche conformation of the C—C—C—C skeleton about an inversion centre. The molecules are densely packed, with short intermolecular contacts between the α‐H and nitrile N atoms.